Bioabsorbable Vascular Scaffold: A Revolution in Coronary Intervention (Cardiovascular Journal, 2014)
Since the advent of percutaneous coronary angioplasty in 1977, immense experiment has been done to improve the outcome of the patients with coronary artery disease. Lot of trials have been done with angioplasty, bare metal stents, drug eluting stents, drug eluting balloons and other devices. Bioabsorbable vascular stents are relatively newcomers in this field with a lot of hope. We tried to update the latest status of Bioabsorbable vascular stents in this review, specially the short and midterm safety and efficacy and some of their limitations. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18359 Cardiovasc. j. 2014; 6(2): 149-163